The Effect Of Personal Values On Organizational Commitment - Zainul Abidin, Salzainna (2004)
The main purpose of this study is to access the relationship between personal values and organizational commitment. The scope of the study focuses on the study by Rokeach, “The Nature of Human Value” and Commitment by Meyer and Allen (1991). This study may shed light to the organization to place greater emphasis on the strategic management of Human Resources in order to gain competitive edge in International markets.